The Early Development of Shafi'is Rules on Mudarabah - Shaharuddin, A.; Gleave, R.E (Universiti Sains Islam Malaysia, 2024)
This paper investigates the development of Shafi'is rules on mudarabah from the second until the sixth century Hijri. The investigation is carried out based on the analysis of itab al-Umm of al-Shafi'i (d.204), al-Muhadhdhab of al-Shirazi (d.472), al-Wajiz of al-Ghazali (d.505) and al-Minhaj of al-Nawawi (d.676). It is found that the mudarabah rules were in preliminary stage during the time of al-Shafi'i and had been developed gradually in the later centuries. As evident in the text of al-Shirazi, the rules most probably finalised during the fourth century. The findings confirm the majority of Western scholars opinion in which argue that the institution of madhhab did not emerged during the lifetime of the eponyms but sometimes after their death.